Uncertain Place: a Spectral Ethnography of Haunted Experience in Perth, Western Australia - Tibbs Johansson, Clea (Curtin University, 2022)
This research redresses the over-determinism of temporality in the literature on haunting by paying critical and creative attention to the ghost’s spatial dimensions. Using the city of Perth as a field site, it examines what the place of Perth, including the case study of Brookfield Place, contributes to knowledge on the spatiality of the ghost through a spectral ethnography